(untitled) (Clinics, 2008)
OBJECTIVE: To evaluate the effects of estrogen treatment in combination with gestrinone on an experimental rat model of endometriosis. METHODS: Uterine transplants were attached to the peritoneum of female Wistar rats via a surgical autotransplantation technique. The implanted area was measured during the proestrus phase and after hormonal treatment. We performed morphometric analysis and examined the macroscopic and morphometric alterations of endometrial implants after hormonal treatment in ovariectomized rats. RESULTS: The high dose of estrogen caused macroscopic increases in the endometrial implant group compared with other groups, which were similar to increases in the proestrus phase. The low dose showed morphometric development of implants, such as an increase in number of endometrial glands, leukocyte infiltration and mitosis. Gestrinone antagonized both doses of estrogen. CONCLUSION: Our findings suggest that gestrinone antagonizes estrogen's effects on rat peritoneal endometrial implants.